Deposição de calda e controle de ferrugem asiática (Phakopsora pachyrhizi) em função do equipamento de pulverização terrestre utilizado na cultura da soja - Londero, Guilherme Pilar (2021)
The efficiency of existing products for controlling Asian rust has been gradually decreasing with its constant use. Much of this is linked to inefficient application where it may happen that the product is not reaching the target, in this case, the leaves of the crop. The present technologies are able to reduce the volume of spray solution and the size of drops, but even so, they are deficient in satisfactorily depositing the product in the lower leaves of soybean plants, where the initial infection of Asian rust occurs. The objective of this work was to identify which spraying equipment in terrestrial application was able to distribute the product more homogeneously in the soybean plant and which contributed to the efficiency of product control. The experiment was carried out in the years 2017/18 and 2018/19. The experimental design used was in bands, in a two-factor scheme (2X4). The first factor was composed of two cultivars of similar cycles, but of different statures and leaf distributions. The second factor was: cone and 3-D hydraulic tips, rotary disk atomizer and electrostatic system. Grout deposition assessments were made in the upper, middle and lower third of the crop; rust severity, thousand grain weight and productivity.